Current Research in Risk-aware Business Process Management―Overview, Comparison, and Gap Analysis - Suriadi, Suriadi; Weiß, Burkhard; Winkelmann, Axel; ter Hofstede, Arthur H.M.; Adams, Michael; Conforti, Raffaele; Fidge, Colin; La Rosa, Marcello; Ouyang, Chun; Pika, Anastasiia; Rosemann, Michael; Wynn, Moe (Communications of the Association for Information Systems, 2014)
The management of risk in business processes has been the subject of active research in the past few years. Potentially, many benefits can be obtained by integrating the two traditionally separated fields of risk management and business process management, including the ability to minimize risks in business processes by design and to mitigate such risks at run time. While there has been an increasing amount of research aimed at delivering such an integrated system, these research efforts vary in terms of scope, goals, and functionality. Through the systematic collection and evaluation of relevant literature, this article compares and classifies current approaches in the area of risk-aware business process management in order to expose and explain current research gaps. The process through which relevant literature was collected, filtered, and evaluated is also detailed. Finally, a research agenda is proposed.